Thank you for the opportunity to help you with your question!
-3=x+x+x The first task you want to accomplish is to put like terms together. The right side of the equation has 3 like terms because they are all terms of x. x+x+x = 3x just as 1+1+1=3. The equation now becomes...
Now divide both sides by 3. -3/3=-1 and 3x/3=x
This is the solution.
Please let me know if you need any clarification. I'm always happy to answer your questions.
Oct 26th, 2015
Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.